2009
DOI: 10.1038/aps.2009.54
|View full text |Cite
|
Sign up to set email alerts
|

Ric-3 chaperone-mediated stable cell-surface expression of the neuronal α7 nicotinic acetylcholine receptor in mammalian cells

Abstract: Aim: Studies of the α7-type neuronal nicotinic acetylcholine receptor (AChR), one of the receptor forms involved in many physiologically relevant processes in the central nervous system, have been hampered by the inability of this homomeric protein to assemble in most heterologous expression systems. In a recent study, it was shown that the chaperone Ric-3 is necessary for the maturation and functional expression of α7-type AChRs [1] . The current work aims at obtaining and characterizing a cell line with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 36 publications
0
23
0
1
Order By: Relevance
“…Human α7 AChRs have been expressed alone or with RIC-3 in several different cell lines [31], [32], [33], [34], [35]. These have provided varying degrees of success at detecting function.…”
Section: Discussionmentioning
confidence: 99%
“…Human α7 AChRs have been expressed alone or with RIC-3 in several different cell lines [31], [32], [33], [34], [35]. These have provided varying degrees of success at detecting function.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of native rat hippocampal ␣7 nAChRs reported a mean single-channel conductance of 91.5 pS, and although a single Gaussian function did not provide a good fit of the amplitude distribution, it was not possible to identify unambiguously multiple conductance levels (Mike et al, 2000). In addition, studies of human recombinant ␣7 nAChRs expressed in SHEP1 cells have identified "two to three different levels of channel amplitudes" (Vallés et al, 2009). Likewise, studies of native chick ␣7 nAChRs identified multiple conductance levels (Nai et al, 2003).…”
mentioning
confidence: 99%
“…Nicotine exposure causes an upregulation of nicotinic AChRs in brain as well as in vitro , and a possible explanation of this effect is through the chaperoning by nicotine [90], [91], [92]. The RIC-3 is a chaperone that upregulates the expression of α7 nAChRs in oocytes [93], [94], [95], [96]. Interestingly, RIC-3 has no effect on the expression of α9 receptors [40], [97].…”
Section: Discussionmentioning
confidence: 99%